Versican expression level in cumulus cells is associated with human oocyte developmental competence. (3rd May 2020) - Shen, Qiuzi; Chen, Mei; Zhao, Xue; Liu, Yu; Ren, Xinling; Zhang, Ling
ABSTRACT: To study the relationship between the expression of 10 selected genes in cumulus cells and the corresponding oocyte development competence, and the effect of patient age and body mass index on gene expression of cumulus cells, we collected 354 cumulus cell masses associated with individual oocyte from 48 women. The expression levels of the genes involved in glucose metabolism ( PFKP, PKM2, LDHA and GFPT ) and expansion ( HAS2, VCAN, TNFAIP6, PTGS2, PTX3 and SDC4 ) in cumulus cells were detected by reverse transcription polymerase chain reaction. These were compared among oocyte maturity, fertilization, embryo morphology and implantation, and analyzed the effect of the subject's age and body mass index. Cumulus cell PFKP expression from mature oocytes was higher than those from immature oocytes (P = 0.014), and VCAN expression was higher from oocytes that developed into high-quality embryos (P = 0.024). TNFAIP6 expression in cumulus cells from fertilized oocytes was lower than that from unfertilized oocytes (P = 0.044). The levels of VCAN, TNFAIP6, PTX3 and SDC4 were changed significantly as a function of the subject's age and body mass index. In conclusion, the level of VCAN expression in cumulus cells is positively correlated with the early embryo morphology score, and with further development could perhaps be used to evaluate oocyte developmental competence to complement embryonic morphological assessment. Abbreviations: CCs: cumulus cells; GDF9: growth differentiation factor 9; BMP15: bone morphogenetic protein 15; PTGS2: prostaglandin synthase 2; HAS2: hyaluronic acid synthase 2; VCAN: versican; GREM1: gremlin 1; PFKP: phosphofructokinase, platelet; PKM2: pyruvate kinase isozyme type M2; LDHA: lactic dehydrogenase; GFPT: glucosaminefructo-6-phosphate transaminase; TNFAIP6: tumor necrosis factor 6 protein; PTX3: penetrin 3; SDC4: syndecan-4; BMI: body mass index; MD: median values; IQR: interquartile range; FSH: follicle-stimulating hormone; LH: luteinizing hormone; HCG: human chorionic gonadotropin; ICSI: intracytoplasmic sperm injection; GnRH: gonadotropin-releasing hormone; hMG: human menopausal gonadotropin; GV: germinal vesicle; M I: metaphase I; M II: metaphase II; cDNA: complementary DNA; SD: standard deviation.